High developmental temperature leads to low reproduction despite adult temperature. (January 2021) - Santos, Marta A.; Carromeu-Santos, Ana; Quina, Ana S.; Santos, Mauro; Matos, Margarida; Simões, Pedro
Abstract: Phenotypic plasticity can help organisms cope with changing thermal conditions and it may depend on which life-stage the thermal stress is imposed: for instance, exposure to stressful temperatures during development can trigger a positive plastic response in adults. Here, we analyze the thermal plastic response of laboratory populations of Drosophila subobscura, derived from two contrasting latitudes of the European cline. We measured reproductive performance through fecundity characters, after the experimental populations were exposed to five thermal treatments, with different combinations of developmental and adult temperatures (14 °C, 18 °C, or 26 °C). Our questions were whether (1) adult performance changes with exposure to higher (or lower) temperatures during development; (2) flies raised at lower temperatures outperform those developed at higher ones, supporting the "colder is better" hypothesis; (3) there is a cumulative effect on adult performance of exposing both juveniles and adults to higher (or lower) temperatures; (4) there is evidence for biogeographical effects on adult performance. Our main findings were that (1) higher developmental temperatures led to low reproductive performance regardless of adult temperature, while at lower temperatures reduced performance only occurred when colder conditions were persistent across juvenile and adult stages; (2) flies raised at lower temperatures did not always outperform those developed at other temperatures; (3) there were no harmful cumulative effects after exposing both juveniles and adults to higher temperatures; (4) both latitudinal populations showed similar thermal plasticity patterns. The negative effect of high developmental temperature on reproductive performance, regardless of adult temperature, highlights the developmental stage as very critical and most vulnerable to climate change and associated heat waves. Highlights: Thermal plasticity was analyzed in two Drosophila subobscura populations from contrasting latitudes. Higher developmental temperature led to lower fecundity regardless of adult temperature. No cumulative effect on reproduction of exposing both juveniles and adults to higher temperature. Reduced reproductive performance of lifetime exposure to lower temperature. Both latitudinal populations showed similar thermal plasticity patterns.